Microbiology - Sharma, Dushyant Kumar (Oxford, UK : Alpha Science International Ltd., 2013)
MICROBIOLOGY is the study of microorganisms - organisms which are too small to be seen with unaided eyes. They are present everywhere in our environment. They act both as our friend and foe. They include bacteria, fungi, virus, protozoa and algae. The book deals with various aspects of microorganisms - diversity of microbial life, their physiology and genetics, importance of microorganisms to mankind, methods to control them and tools and techniques to study them. It not only focuses on the fundamentals but also covers the application aspect of the subject. The book will help the readers to explore and understand the fascinating world of microorganisms.
pt. I. Tools and techniques in microbiology -- Microscopy -- Staining and staining techniques -- pt. II. Microbial world -- Classification of microorganisms -- Bacteria -- Virus -- Fungi -- Algae -- Protozoa -- pt. III. Microbial growth, metabolism and genetics -- Growth of microorganisms -- Culture of microorganisms -- Microbial metabolism -- pt. IV. Environmental and applied microbiology -- Microbial genetics -- Microbiology of soil -- Microbiology of water -- Microbiology of food -- Industrial microbiology -- pt. V. Microbiology and health -- Basic concepts of immunology -- Antigen-antibody reaction -- Vaccines -- Microorganisms and diseases -- pt. VI. Control of microorganisms -- Control of microorganisms -- Physical methods of microbial control -- Chemical methods of microbial control -- Antimicrobial drugs.
Includes index.
Print version record.
Added to collection customer.56279.3
Keywords: Microbiology; Microbiology; Microbiologie; microbiology; Microbiology